Perlindungan Hak Kekayaan Intelektual Dalam Rangka Memberikan Kepastian Hukum di Indonesia - Burhanudin; Tata Eliestiana Dyah A (Fakultas Hukum Universitas Nahdlatul Ulama Nusa Tenggara Barat, 2025)
The advancement of a knowledge-based economy positions intellectual property rights as an important legal instrument for fostering innovation and safeguarding creative works. Nevertheless, the plurality of intellectual property regulations continues to generate issues related to normative consistency and legal certainty. This study aims to examine the consistency of legal norms governing intellectual property protection and to evaluate the fulfillment of the principle of legal certainty within Indonesia’s legal regulatory system. The research employs a normative legal method using statutory and conceptual approaches. Legal analysis is carried out through grammatical, systematic, and teleological interpretation based on legal theory and legal principles. The findings reveal that, first, intellectual property legal norms are generally consistent in recognizing exclusive rights as the foundation of legal protection, although disparities remain in the regulation of enforcement mechanisms and sanctions across different statutes. Second, intellectual property protection norms have, in principle, satisfied the requirement of legal certainty through clear regulation of protected objects, legal subjects, and protection periods; however, further strengthening of normative consistency is still necessary. Harmonization of norms in accordance with the principles governing legislative formation is therefore essential to achieve equitable intellectual property protection